Design and Manufacturing of a Variable Speed Control Moment Gyro for an Agile Micro-Satellite Attitude Control Simulator - Ali Reza Aghalari; Ahmad Kalhor; Farhad Shamim (فصلنامه علوم و فناوری فضایی, 2015)
In this paper, a designing procedure of a Variable Speed Control Moment Gyro (VSCMG) for performing an agile maneuver in an attitude control simulator is described, then a prototype is fabricated and finally the test results are presented. The design of actuator mechanism is based on simulator limitations (power consumption, dimensions and weight, simplicity) and direction of produced torque.Two DC electrical motors are used for controlling the angular velocity of flywheel and the gimbal slew rate. The motors controller and driver units are designed and implemented, so that the maximum accuracy, minimum errors and best response time could be accessible. Structural Design is based on strength, stiffness, volume and weightalso Necessary analysis are performed using ANSYS. Finally the functional tests of actuator such as measuring the produced torque (using simulator and load transducer), accuracy of gimbal position and gimbal slew rate, accuracy of flywheel rotational speed and power consumption are performed and then the results are presented.